2008
DOI: 10.1063/1.2988261
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of Ge profiles across SiGe wetting layers on Si (001)

Abstract: The peak positions in photoluminescence spectra of Ge wetting layers (WL) deposited at 700 °C were measured versus the Ge coverage with an extremely high relative resolution of 0.025 monolayers. A nearly linear redshift of the peaks with increasing Ge coverage is observed. We derived quantitative WL composition profiles by fitting this shift, and its dependence on the deposition temperature of the capping layer (Tc), to results of band structure calculations. Despite the high growth temperature, the Ge content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 19 publications
4
35
0
Order By: Relevance
“…21 In Fig. 3͑c͒ the shift of the no-phonon ͑NP͒ WL transition energy is plotted versus ⌰ Ge for T g = 625 and 700°C.…”
Section: Experiments: Growth Photoluminescence and Afmmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In Fig. 3͑c͒ the shift of the no-phonon ͑NP͒ WL transition energy is plotted versus ⌰ Ge for T g = 625 and 700°C.…”
Section: Experiments: Growth Photoluminescence and Afmmentioning
confidence: 99%
“…3͑b͔͒ was used in Ref. 21 to derive quantitative Ge profiles in the WL, which resulted in a maximum Ge content of Ϸ85%. When the domes appear ͑4.25 ML at T g = 700°C and 4.92 ML at T g = 625°C͒ we see an abrupt blueshift of the WL PL signal by 0.06 eV ͑Figs.…”
Section: Experiments: Growth Photoluminescence and Afmmentioning
confidence: 99%
“…SAM analysis 15 shows that the Ge content of the over-layer is approximately constant within the nucleation region (x < 20 lm) and its average value decreases from $0.8 at 600 C to $0.64 at 700 C. This temperature dependence reflects the thermally activated nature of the Si incorporation. When our results are compared to typical MBE data, where Ge concentration values of the wetting layer greater than 0.86 have been found even at 700 C, 26 it is evident that the thermal diffusion from a local source results in an enhanced intermixing within the OL, whose origin will be discussed in details later.…”
Section: Resultsmentioning
confidence: 72%
“…In MBE, a Ge-rich wetting layer (c WL Ge > 0:86) forms even at high temperatures (T % 700 C). 26 When the WL thickness exceeds its critical value, faceted Ge-rich islands nucleate and grow at the expense of smaller ones via a coarsening process. 38 islands, digging deeply into the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…5,[10][11][12][13][14][15][16][17][18][19][20][21][22] Atomic-scale modeling of Ge growth on Si(001) suggested that entropy limits the wetting tendency of Ge, thus smearing the interface. 18 High-resolution Rutherford backscattering spectrometry (HR-RBS) studies demonstrated that intermixing extends as deep as four layers upon thermal annealing.…”
Section: Introductionmentioning
confidence: 99%